In vitro inhibition of Pseudomonas aeruginosa PAO1 biofilm formation by DZ2002 through regulation of extracellular DNA and alginate production - Jiaze Dai; Wenying Luo; Fei Hu; Si Li (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionPseudomonas aeruginosa (P. aeruginosa) is a common pathogen associated with biofilm infections, which can lead to persistent infections. Therefore, there is an urgent need to develop new anti-biofilm drugs. DZ2002 is a reversible inhibitor that targets S-adenosylhomocysteine hydrolase and possesses anti-inflammatory and immune-regulatory activities. However, its anti-biofilm activity has not been reported yet.Methods and resultsTherefore, we investigated the effect of DZ2002 on P. aeruginosa PAO1 biofilm formation by crystal violet staining (CV), real-time quantitative polymerase chain reaction (RT-qPCR) and confocal laser scanning microscopy (CLSM). The results indicated that although DZ2002 didn’t affect the growth of planktonic PAO1, it could significantly inhibit the formation of mature biofilms. During the inhibition of biofilm formation by DZ2002, there was a parallel decrease in the synthesis of alginate and the expression level of alginate genes, along with a weakening of swarming motility. However, these results were unrelated to the expression of lasI, lasR, rhII, rhIR. Additionally, we also found that after treatment with DZ2002, the biofilms and extracellular DNA content of PAO1 were significantly reduced. Molecular docking results further confirmed that DZ2002 had a strong binding affinity with the active site of S-adenosylhomocysteine hydrolase (SahH) of PAO1.DiscussionIn summary, our results indicated that DZ2002 may interact with SahH in PAO1, inhibiting the formation of mature biofilms by downregulating alginate synthesis, extracellular DNA production and swarming motility. These findings demonstrate the potential value of DZ2002 in treating biofilm infections associated with P. aeruginosa.